A CMOS Low-Power Optical Front-End for 5 Gbps Applications. Issue 1 (2nd January 2018) - Zohoori, Soorena; Dolatshahi, Mehdi
ABSTRACT: In this paper, a new low-power optical receiver front-end is proposed in 90 nm CMOS technology for 5 Gb/s AApplications. However, to improve the gain-bandwidth trade-off, the proposed Trans-Impedance Amplifier (TIA) uses an active modified inverter-based topology followed by a common-source amplifier, which uses active inductive peaking technique to enhance the frequency bandwidth in an increased gain level for a reasonable power consumption value. The proposed TIA is analyzed and simulated in HSPICE using 90 nm CMOS technology parameters. Simulation results show a 53.5dBΩ trans-impedance gain, 3.5 GHz frequency bandwidth, 16.8pA/√Hz input referred noise, and 1.28 mW of power consumption at 1V supply voltage. The Optical receiver is completed using three stages of differential limiting amplifiers (LAs), which provide 27 dB voltage gain while consume 3.1 mW of power. Finally, the whole optical receiver front-end consumes only 5.6 mW of power at 1 V supply and amplifies the input signal by 80 dB, while providing 3.7 GHz of frequency bandwidth. Finally, the simulation results indicate that the proposed optical receiver is a proper candidate to be used in a low-power 5 Gbps optical communication system.